Development of a 3D Printed Biologically Inspired Monoped Self-Balancing Robot - Denis Manolescu; Emanuele Lindo Secco (Association for Scientific Computing Electronics and Engineering (ASCEE), 2023)
The development of lightweight, agile robots built with a high degree of efficiency and precision is a complex and particularly challenging task. In Robotics, the perspectives of such systems have the potential to reimagine and reevaluate space and planetary explorations while enhancing the human ability to reach and analyze different environments. This research evaluates ways to build a single-leg robot capable of self-balancing on any terrain with the prospect of omnidirectional saltation steering. This report will go through the process of designing a 1-degree of freedom, balanced robot while evaluating various hardware options in motion control and data feedback. Based on these research findings, this paper will also discuss the difficulties and issues encountered and the approach to solving them.